URGENSI KESELAMATAN NAVIGASI PADA PENGANGKUTAN KOMODITAS DI JALUR PELAYARAN DI KAWASAN ASIA-PASIFIK - Aji Setiyo Kusumo (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This research aims to analyze the urgency of safety navigation procedures which play an important role in ensuring the safety of life at sea. Then, the author also analyzes the components of safety navigation procedures that have important role in the shipping sector in the Asia-Pacific Region. Where the level of intensity of shipping and international trade in the area is very high. This is normative research with a perspective using primary and secondary legal materials. The technique of collecting legal materials is a literature study which is equipped with a deduction technique to analyze the material. The results show that there are twelve navigation safety procedures that play an important role in ensuring the safety of life at sea. Where navigation safety procedures need to be understood, regulated, and further improved to improve efficiency, security and shipping safety. Therefore, navigational safety plays a very vital role in the field of transporting commodities at sea, especially in shipping lanes in the Asia-Pacific Region.